2005
DOI: 10.1590/s0037-86822005000100007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative clinical and ultrasound study of egg-negative and egg-positive individuals from Schistosoma mansoni low morbidity endemic areas, and hospitalized patients with hepatosplenic disease

Abstract: Estudo clínico comparativo e ultra-sonografia entre indivíduos negativos e positivos para Schistosoma mansoni em áreas endêmicas de baixa morbidade e pacientes hospitalizados com doença hepatosplênica G2 and G3, respectively, in 11.1, 12.1 and 26.3%. In G1, G2 and G3, periportal with periportal echogenicity (3-6mm); and G4 -9 hepatosplenic patients with periportal echogenicity (> 6mm). Hepatomegaly detected by physical examination of the abdomen evaluated in the midclavicular line was verified in G1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…However, this span of time was not sufficient to reduce the spleen size. These results tend to confirm that the chemotherapy favors involution of liver fibrosis (12,34). In addition, our study confirmed that a decrease in worm burden favors the reversal of liver fibrosis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, this span of time was not sufficient to reduce the spleen size. These results tend to confirm that the chemotherapy favors involution of liver fibrosis (12,34). In addition, our study confirmed that a decrease in worm burden favors the reversal of liver fibrosis.…”
Section: Discussionsupporting
confidence: 85%
“…The direct evaluation of the intensity of hepatic fibrosis in large cohorts may be carried out by abdominal ultrasound examination, a technique that is noninvasive, safe, reliable, and relatively inexpensive. Moreover, there are several criteria available for grading the severity of the disease based on the determination of liver and spleen parameters (1,12,32,34,36). In the present study we evaluated the morbidity (by ultrasound analysis) and the cel-lular immune response of schistosomiasis patients before and one year after treatment with praziquantel.…”
mentioning
confidence: 99%
“…Liver size, portal vein diameter, thickness of the walls of the central and peripheral portal branches, spleen size, and splenic and mesenteric vein diameters were assessed using a conventional portable ultrasound instrument (ultrasonic diagnostic instrument model EUB-200; Hitachi, Tokyo, Japan). Periportal thicknesses were evaluated according to the established criteria for the classification of hepatic fibrosis, with some modifications (1,25). In this classification, the degree of fibrosis was determined from the central and peripheral echogenic periportal thickness of the liver portal system.…”
Section: Methodsmentioning
confidence: 99%
“…Estudos realizados com pessoas e camundongos infectados têm caracterizado a esquistossomose como uma doença predominantemente Th2, implicando a produção de citocinas advindas desse perfil como a causa da morbidade do hospedeiro (DE JESUS et al, 2004;MAGALHÃES et al, 2005). Entretanto, dados de um trabalho realizado com modelos experimentais sugerem que a resposta Th2 é importante para a sobrevivência do paciente (FALLON et al, 2000).…”
Section: A Resposta Imune Na Esquistossomoseunclassified